Associations between diffusion MRI microstructure and cerebrospinal fluid markers of Alzheimer's disease pathology and neurodegeneration along the Alzheimer's disease continuum. Issue 1 (4th December 2022) - Moody, Jason F.; Dean, Douglas C.; Kecskemeti, Steve R.; Blennow, Kaj; Zetterberg, Henrik; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Wild, Norbert; Carlsson, Cynthia M.; Johnson, Sterling C.; Alexander, Andrew L.; Bendlin, Barbara B.
Abstract: Introduction: White matter (WM) degeneration is a critical component of early Alzheimer's disease (AD) pathophysiology. Diffusion‐weighted imaging (DWI) models, including diffusion tensor imaging (DTI), neurite orientation dispersion and density imaging (NODDI), and mean apparent propagator MRI (MAP‐MRI), have the potential to identify early neurodegenerative WM changes associated with AD. Methods: We imaged 213 (198 cognitively unimpaired) aging adults with DWI and used tract‐based spatial statistics to compare 15 DWI metrics of WM microstructure to 9 cerebrospinal fluid (CSF) markers of AD pathology and neurodegeneration treated as continuous variables. Results: We found widespread WM injury in AD, as indexed by robust associations between DWI metrics and CSF biomarkers. MAP‐MRI had more spatially diffuse relationships with Aβ42/40 and pTau, compared with NODDI and DTI. Discussion: Our results suggest that WM degeneration may be more pervasive in AD than is commonly appreciated and that innovative DWI models such as MAP‐MRI may provide clinically viable biomarkers of AD‐related neurodegeneration in the earliest stages of AD progression.